Attributes facilitating solid waste separation at source practice among household - Nur Azzlin Mangsor, 1990-, author 610953 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Pengurusan Aset dan Fasiliti)